The t-PA-encapsulated PLGA nanoparticles shelled with CS or CS-GRGD alter both permeation through and dissolving patterns of blood clots compared with t-PA solution: An in vitro thrombolysis study - Wang, Shoei-Shen; Chou, Nai-Kuan; Chung, Tze-Wen (Journal of biomedical materials research. Part A, 2009)
Accelerated thrombolysis by pressure‐driven permeation has been demonstrated in in vitro and in vivo animal models by using plasminogen activators (PAs) encapsulated liposomes or PEG microparticles. Recent reports have also described acceleration of thrombolysis using tissue type PA (t‐PA) encapsulated in PLGA nanoparticles (NPs) coated with chitosan (CS) or CS‐GRGD by interactions between the NPs and blood clots. However, the permeation through and dissolving patterns in thrombolysis with the aforementioned microparticles or NPs, which may be clinically relevant to the recovery status of the posttreatments, have not been reported. Therefore, this work studied such phenomena in thrombolysis with t‐PA encapsulated in NPs. The t‐PA solution and the NPs exhibited distinctly different permeation patterns of dissolved clots. Plasma permeates through clots showed a stream flow or burst flow phenomena when lyzed with NPs shelled with CS or CS‐GRGD, respectively, whereas a diffusion pattern was observed in those lyzed with t‐PA solution. At the outlet position of clots, the clots dissolved with PLGA/CS and PLGA/CS‐GRGD NPs revealed extremely rough surfaces to a depth of 100 μm, indicating that a cross‐permeation direction of clot lysis occurred, while those dissolved with t‐PA solution showed slightly rough surfaces to a depth of 12 μm. Permeation through and clot dissolution patterns of thrombolysis with t‐PA encapsulated in NPs shelled with CS or CS‐GRGD distinctly differed from those dissolved with t‐PA solutions in this in vitro thrombolysis model, These findings may be relevant to posttreatment of patients with conventional PA thrombolysis. © 2008 Wiley Periodicals, Inc. J Biomed Mater Res, 2009